2017
DOI: 10.1186/s40562-017-0089-0
|View full text |Cite
|
Sign up to set email alerts
|

Using ultra-low frequency waves and their characteristics to diagnose key physics of substorm onset

Abstract: Substorm onset is marked in the ionosphere by the sudden brightening of an existing auroral arc or the creation of a new auroral arc. Also present is the formation of auroral beads, proposed to play a key role in the detonation of the substorm, as well as the development of the large-scale substorm current wedge (SCW), invoked to carry the current diversion. Both these phenomena, auroral beads and the SCW, have been intimately related to ultra-low frequency (ULF) waves of specific frequencies as observed by gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 61 publications
3
12
0
Order By: Relevance
“…Pi1 period waves, with their shorter periods, are often observed at similar times to the Pi2 pulsations (Bosinger & Yahnin, ; Jacobs et al, ). More recent work has often used a combination of the two period bands, often denoted Pi1‐2 and spanning the period band 24–96 s (e.g., Milling et al, ; Murphy et al, ; Rae et al, , ), which have been shown to be coincident with auroral beads (Rae, Mann, Murphy, et al, ; Walsh et al, ). Additionally, the spectra of ULF waves around substorm onset has been shown to be a power law, with no clear break separating the Pi1 and Pi2 wave bands (Murphy et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Pi1 period waves, with their shorter periods, are often observed at similar times to the Pi2 pulsations (Bosinger & Yahnin, ; Jacobs et al, ). More recent work has often used a combination of the two period bands, often denoted Pi1‐2 and spanning the period band 24–96 s (e.g., Milling et al, ; Murphy et al, ; Rae et al, , ), which have been shown to be coincident with auroral beads (Rae, Mann, Murphy, et al, ; Walsh et al, ). Additionally, the spectra of ULF waves around substorm onset has been shown to be a power law, with no clear break separating the Pi1 and Pi2 wave bands (Murphy et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The preonset aurora scenario suggests that the fast earthward flow evolves an onset instability, such as ballooning instability, leading to initial auroral brightening (Nishimura et al, 2014). Ballooning mode waves may be excited a few minutes before initial brightening (as determined with a spacecraft-borne auroral imager) (Saito et al, 2008). The time difference between the arrival of the preonset aurora at the onset arc and initial brightening that Nishimura et al (2010) showed seems consistent with the growth time of an instability.…”
Section: Summary and Open Questionsmentioning
confidence: 77%
“…Rae et al (2017) determine the relative timing between sudden increases in amplitude, or onsets, of different ultra-low-frequency (ULF) wave bands during substorms. They show that differing onset times and spatial expansion exist for Pi1, Pi1-2, and Pi2 waves in the ionosphere during substorms.…”
Section: Ground Magnetic Perturbationmentioning
confidence: 99%